O programa de fomento às escolas de ensino médio em tempo integral em Minas Gerais: os processos de regulação transnacional, nacional e local - Camila Raquel Benevenuto de Andrade (2021)
The present doctoral research has the main objective of identifying, describing and analyzing the processes and developments of the formulation and implementation of the policy for full-time education in the stage of High School in the State of Minas Gerais, proposed by Law 13,415 of 2017, which enacted the reform of this stage of basic education in Brazil. This law proposes the implementation of the Full-Time Secondary Schools Promotion Program (EMTI), which promises to progressively expand schooling time in high school, from the current four to seven hours a day. The theoretical path used to analyze the collected data is the theory of regulation and public action, based on authors such as João Barroso and Cristian Maroy, considering that this theory considers not only state action in the process of implementing a policy, but also the actors involved in it, resulting in multiple regulations (institutional, control and autonomous) at the local, national and transnational level. For this work, qualitative methodology was used, with field research in three schools in the state of Minas Gerais. The data collection techniques used were observation in research schools, semi-structured interviews with school professionals (directors, coordinators, teachers and students) and the MG State Department of Education (SEE / MG), in addition to documentary sources. The data show that the subjects of the schools have a relative autonomy in their actions, based on the orientations coming from SEE / MG and with this they have created their own strategies for implementing the activities proposed by the program, even if they are in specific aspects, adapting the that EMTI was predicted to work conditions and infrastructure existing in schools, at the same time that the State exercises its role as regulator of educational policies, through institutional regulation and control. It also highlights the role of international organizations (World Bank, UNESCO and OECD) in this process, which, through their guidelines, seek to influence the directions and directions for the MS, as dictated by the globally structured agenda for education.